Exercise training as an adjunct to orlistat therapy reduces oxidative stress in obese subjects - Ozcelik, O; Ozkan, Y; Karatas, F; Kelestimur, H (Tohoku Univ Medical Press, 2005)
OZCELIK, O., OZKAN, Y., KARATAS, F. and KELESTIMUR, H. Exercise Training as an Adjunct to Orlistat Therapy Reduces Oxidative Stress in Obese Subjects. Tohoku J. Exp. Med., 2005, 206 (4), 313-318 - The anti-obesity drug orlistat promotes weight loss and improves obesity-related risk factors, but its effect on oxidative stress is not clear yet. Orlistat reduces dietary fat absorption, which may have effects on fat soluble vitamins especially the antioxidant vitamins A and E. The aim of this study was to determine and compare the effects of weight loss achieved by orlistat therapy and a combination of orlistat with aerobic exercise training on lipid peroxidation and antioxidative defense in obese subjects. Total of 24 obese subjects were randomly assigned to receive 12-week treatment with hypocaloric diet-orlistat (120 mg three times daily) (DO group) or dietorlistat-exercise (DOE group). Serum levels of malondialdehyde (MDA), a marker for lipid peroxidation, and vitamins A and E were measured by high performance liquid chromatography at baseline and at the end of the treatment. Body weight and fat mass were significantly reduced in the two groups (p < 0.001). In the DO group, the MDA levels remained unchanged (p = 0.59), while vitamins A (p < 0.01) and E (p < 0.001) were significantly decreased. In contrast, the subjects treated with DOE exhibited marked decreases in MDA (p = 0.002) and a small but significant decrease in vitamins A (p = 0.003) and E (p = 0.003). Thus, orlistat therapy alone caused a significant reduction in antioxidative capacity without affecting oxidative stress, whereas orlistat in combination with exercise training provided a significant decrease in MDA levels. The beneficial effect of aerobic exercise as an adjunct to the orlistat therapy is of importance with regard to the obesity-associated risk factors. - obesity; body mass index; MDA; orlistat; exercise. (c) 2005 Tohoku University Medical Press.
Keywords: obesity; body mass index; MDA; orlistat; exercise